Peak Performance Selling : How to Increase Your Sales by 80% in 8 Weeks. - Johnson, Kerry (Kerry L.) (G & D Media, 2019)
Using these step-by-step techniques, you will be able to get past your self-defeating behaviors, stay on a weekly business plan, and nearly double your business. All in eight weeks!